Escrituração contábil fiscal: percepções no processo de implantação e execução - Fernandes, Juliana Margarida (2016)
The international convergence of financial statements required a constant improvement from the professional accounting aligned with global best practices. Within this process of change, the government also had to adapt by editing a new Law for Corporations (nº 11.638/2007) which had also to be corrected through the Transition Tax Regime published in Law (nº 11.941/2009). Another achievement made by government in regard to evoking the importance of electronic media to generate reliable and useful information, especially in a timely manner. The government has been aware of this new need for agile information and with the use of electronic means has achieved broad objectives of benefits such as, for example, sharing the information provided in all spheres of government, relieving the taxpayer and avoiding possible fraud. Given this unique setting, in which the government needs to converge to the taxpayers’ needs, the Fiscal Bookkeeping project has been created. This project aimed to exempt businesspeople from delivery accessory statements (Declaration of Economic and Tax Information of Legal Entities, Counting Book of Taxable Income and Calculation of Book of Social Contribution) and broadcast on Public Digital Bookkeeping System environment FCONT where this represented the tax neutrality, derived from expense, revenue and cost accounts of the Companies and now, all of this information would be prepared and submitted in a single file, the tax Bookkeeping. This paper conducted an exploratory research grounded on a literature review on the subject and a survey conducted through a questionnaire with several companies in which the respondents attended mainly the accounting and tax areas. The main objective of this survey was to capture the companies’ perception regarding this transition from the ancillary obligations to the electronic environment and the government's proposal, especially in regards to cost savings after the implementation of the electronic bookkeeping. All in all, it could be observed in the study group, that there is relatively favorable perception regarding the impact of this process by the companies